Research on reference signal scheme for high-mobility scenarios in the Terahertz frequency band - LIU Liping; BAO Tong; XIN Yu; HU Liujun (Dianxin kexue)
A novel reference signal scheme, E DFT-s-OFDM DMRS was proposed for high-mobility scenarios in the Terahertz band. The proposed scheme involved segmenting the reference signal sequence with cyclic prefix and cyclic suffix into a head and tail reference signal sequence. These sequences were then embedded into the tail and head of each OFDM symbol, respectively. The scheme had the advantage of using a complete reference signal sequence formed by the tail of the preceding OFDM symbol and the head of the following OFDM symbol. This allowed the receiver to perform channel estimation in each OFDM symbol interval, improving the accuracy and real-time performance of channel estimation. Furthermore, adjacent OFDM symbols share identical head and tail reference signal sequences, eliminating the traditional cyclic prefix for each OFDM symbol and improving spectral efficiency. Simulation results demonstrate that this scheme provides more precise channel estimation and greater spectral efficiency than DMRS scheme with 5G NR DFT-s-OFDM waveform for high-mobility scenarios in the Terahertz band.